Movilidad de Aspergillus flavus link ex fries en mazorcas de cinco genotipos de maiz (Zea Mays L.) empleando tres métodos de inoculación (ING) - Villalobos, Néstor (1986)
Three inoculation techniques for evaluating reaction of corn to kernel infection by Aspergillus flavus were tested in the field of five different genotypes. Inoculations were made 20 days after midsilk stage, using 0.5 ml of 105 conidial suspensions. The methods were: a) injection of small amounts of inoculum in each kernel of a vertical row (M1); b) injection in the first well developed kernels around the top part of the ear (M2); c) injection of inoculum in the kernels at the lower part of the ear, forming a semicircle (M3). Two weeks after inoculation ears were harvested, and kernels not wounded were separated according to its position to the inoculated kernels, then surface sterilized and planted on PDA, to determine the infection percentage. M1 and M2 were found very efficient because they produced higher infection levels. M1 is considered the best because it provided a larger number of kernels for assay and was easy to use. No statistical difference was found among genotypes.